The Semantic Field of Ngethok 'to Cut' and Sociocultural Factors in Javanese Society: Sociosemantic Study - Dwi Atmawati (Journal of Language and Literature, 2021)
This research is motivated by the decreasing awareness of some people towards the preservation of the Javanese language, especially the younger generation. In their daily communication, some of them do not speak Javanese but speak Indonesian. In fact, in Javanese, there is a complex and complete lexicon that can express livelihoods, such as farming. At this time, these activities are starting to be abandoned due to technological developments and changing mindsets. This study aims to find and explain the semantic components of the lexicon of the verb ngethok [ngǝthͻ?] 'to cut' and its lexemes and socio-cultural factors contained in the meaning of each lexeme. This research used a qualitative descriptive method and sociosemantic approach. The data was taken in the Borobudur area, Magelang Regency, Central Java Province. Data collection was carried out by interviewing, recording, and taking notes. In this study, three informants were used. The results of this study indicate that the lexicon of the verb ngethok 'to cut' has fifteen lexemes, namely mancung, mapras, mbabat, mbacok, mlathok, munthes, ngarit, nugel, nggraji, nggunting, ngiris, nyacah, nyembeleh, nyeset, and nyigar. Each lexeme has different lexical meanings. The socio-cultural factors of the community that are revealed in the ngethok ‘to cut’ lexicon and its lexemes are people who live in villages and work as farmers, people who work using traditional tools, people have a simple mindset and a strong spirit of mutual cooperation, and people help selflessly.